MODEL PEMBELAJARAN PUISI “CIPIT BARU”: SEBUAH INOVASI PEMBELAJARAN SASTRA BERBASIS MULTIKULTURAL - Ari Kusmiatun (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2016)
Multicultural in Indonesia becomes a portrait of our culturally rich country from its diverse community. It grows to be a demand in the education world to give a good understanding about multiculturalism to Indonesian people. One of the media that can be applied here is poetry learning. Poetry learning which is based on multiculturalism can be applied in various models. One of the innovations in poetry learning containing multicultural education is “cipit baru”. It involves the steps of before, in middle of, and after the poetry creation. It uses thinking approach and is based on problems. The problem presented is related to multiculturalism. This model is intended to be an alternative way in delivering the poetry learning easily and fun and contains multicultural education.